Policy implementation and recommended actions to create healthy food environments using the Healthy Food Environment Policy Index (Food-EPI): a comparative analysis in South AsiaResearch in context - Elisa Pineda; Petya Atanasova; Nalinda Tharanga Wellappuli; Dian Kusuma; Himali Herath; Alexa Blair Segal; Stefanie Vandevijvere; Ranjit Mohan Anjana; Abu Ahmed Shamim; Saira Afzal; Fahmida Akter; Faiza Aziz; et al. (Elsevier, 2024)
Summary: Background: The increasing prevalence of diet-related non-communicable diseases (NCDs) in South Asia is concerning, with type 2 diabetes projected to rise to 68%, compared to the global increase of 44%. Encouraging healthy diets requires stronger policies for healthier food environments. Methods: This study reviewed and assessed food environment policies in Bangladesh, India, Pakistan, and Sri Lanka from 2020 to 2022 using the Healthy Food Environment Policy Index (Food-EPI) and compared them with global best practices. Seven policy domains and six infrastructure support domains were considered, employing 47 good practice indicators to prevent NCDs. Stakeholders from government and non-governmental sectors in South Asia (n = 148) were invited to assess policy and infrastructure support implementation using the Delphi method. Findings: Implementation of food environment policies and infrastructure support in these countries was predominantly weak. Labelling, monitoring, and leadership policies received a moderate rating, with a focus on food safety, hygiene, and quality rather than obesity prevention. Key policy gaps prioritized for attention included front-of-pack labelling, healthy food subsidies, unhealthy food taxation, restrictions on unhealthy food promotion, and improvements in school nutrition standards to combat NCDs. Interpretation: Urgent action is required to expand food policies beyond hygiene and food security measures. Comprehensive strategies targeting NCD prevention are crucial to combat the escalating burden of NCDs in the region. Funding: This research was funded by the NIHR (16/136/68 and 132960) with aid from the UK Government for global health research. Petya Atanasova also acknowledges funding from the Economic and Social Research Council (ESRC) (ES/P000703/1). The views expressed are those of the authors and not necessarily of the NIHR, the UK government or the ESRC.